Differential diagnosis of developmental defects of enamel and associated factors: a crosssectional study conducted with dentists in Southern Brazil - Paula Dresch Portella,; Gabriela Fonseca de Souza,; Juliana Feltrin de Souza,; Luciana Reichert da Silva Assunção, (Revista Sul-Brasileira de Odontologia, 2025)
Enamel development defects (EDD) encompass diverse dental anomalies affecting deciduous and permanent dentition, posing diagnostic challenges crucial for effective clinical management. Objective: Assessing Southern Brazilian dental surgeons’ (DS) knowledge about, and factors associated with, differential diagnosis of EDD. Material and methods: Cross-sectional study utilized an online, anonymous and self-administered questionnaire distributed to actively registered professionals at the Regional Dentistry Council, Paraná State, Brazil, from January to August 2020. Participants were presented with images of different types of EDD and were asked to provide corresponding diagnosis for each defect. Univariate and multivariate Poisson regression analyses with robust variance was employed to assess correlation among factors associated with professionals’ performance in differential diagnosis of EDD. Results: A total of 613 DSs participated in the study, 76.5% of them were women; their mean age was 37.74 years (standard deviation; SD=11.027). The mean number of correct diagnoses was 1.93 (SD=1.121); with only 11.4% of participants achieving 100% accuracy. The frequencies of correct diagnoses were: fluorosis (73.1%), amelogenesis imperfecta (64.4%), hypoplasia (29.7%) and demarcated opacity (25.9%). Holding a Master’s and/or Doctorate degree was associated with larger number of correct diagnoses for all EDD types, except for fluorosis. Participants’ age was associated with higher frequency of correct diagnoses for demarcated opacity and fluorosis. Training in the field of Pediatric Dentistry was associated with a higher number of correct diagnoses for all EDD subtypes(P<0.05). Conclusion: Dental surgeons demonstrated limited knowledge regarding the differential diagnosis of EDD, particularly concerning hypoplasia and demarcated opacity. The findings of this study underscore the necessity of providing specific and continuous training in the differential diagnosis of various EDD types, particularly focusing on demarcated opacity and hypoplasia.